Assessment of social support, expressed emotion and compliance to treatment among hospital admitted schizophrenic patients in Malaysia - Al-Ani, Ali Sabri Radeef; Musa, Ramli; Ali, Syed Masroor; Abu Bakar, Ahmad Zafri (Ektodermal Displazi Grubu, 2017)
One of the important factors that may predict the relapse in schizophrenia is having poor social support, high Expressed Emotion (EE)and poor compliance. The family is an important factor that affects the patient’s mental well-being and outcome, this study aimed to assess the social support, expressed emotion and treatment compliance among hospital admitted schizophrenic patients. A cross sectional study conducted among a sample of 162 patients diagnosed with schizophrenia admitted in psychiatric ward. Various factors were being assessed including age, gender, ethnicity monthly income, duration of the illness, number of admissions to the psychiatric ward, assessment of expressed emotion and compliance with treatment. The multidimensional scale of perceived social support (MSPSS) was used to measures perceived social support. Although there was no significant association between males and female in total scale social support, only the friend subscale social support was found significantly higher in males (p=0.038). Males have significant better compliance to medication than females (p=0.000). The prevalence of concurrent substance abuse was 14.8 % and it is significantly higher among male schizophrenic patients than female patients (p=0.000). There was no significant association between gender and high EE level. Having no history of co-morbid drug misuse (mean=4.39; p=0.039), and having high level of psychoeducation within the family (mean=4,48; p=0.004) were significantly associated with higher mean scores in total scale social support. Efforts to improve social support are essential in managing patients with schizophrenia competently. The level of psychoeducation within the family is a very important factor in relation to patients’ social support. Early detection and intervention toward co-morbid substance use disorder among schizophrenic patients is vital as it has been associated with poor social support. There is no difference between male or female patients in relation to high EE and family intervention should include steps to reduce it in both genders.